2006
DOI: 10.1890/1051-0761(2006)016[2208:dopdti]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Prion Disease Transmission in Mule Deer

Abstract: Chronic wasting disease (CWD), a contagious prion disease of the deer family, has the potential to severely harm deer populations and disrupt ecosystems where deer occur in abundance. Consequently, understanding the dynamics of this emerging infectious disease, and particularly the dynamics of its transmission, has emerged as an important challenge for contemporary ecologists and wildlife managers. Although CWD is contagious among deer, the relative importance of pathways for its transmission remains unclear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
145
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 111 publications
(156 citation statements)
references
References 26 publications
7
145
4
Order By: Relevance
“…An additional experiment by Miller et al showed that CWDinfected carcasses allowed to decay naturally in confined pastures can lead to CWD infections in captive deer, demonstrating the potential for environmental contamination to spread infection [55]. Modelling studies have provided further support that environmental contamination is likely playing a significant role in transmitting CWD [53,56]. Additionally, infectious prions have been demonstrated to bind soil particles and remain infectious to animals by both intracerebral and oral exposure routes [37,38].…”
Section: Disease Control Challenges Posed By Cwdmentioning
confidence: 99%
“…An additional experiment by Miller et al showed that CWDinfected carcasses allowed to decay naturally in confined pastures can lead to CWD infections in captive deer, demonstrating the potential for environmental contamination to spread infection [55]. Modelling studies have provided further support that environmental contamination is likely playing a significant role in transmitting CWD [53,56]. Additionally, infectious prions have been demonstrated to bind soil particles and remain infectious to animals by both intracerebral and oral exposure routes [37,38].…”
Section: Disease Control Challenges Posed By Cwdmentioning
confidence: 99%
“…The discrete-time analogs of continuous-time disease models (e.g., Miller et al 2006, Yee et al 2011) are more tractable because data taken at discrete intervals can be matched with model predictions. Parameter estimation and analysis of systems of discrete-time equations, also called matrix models, have seen broad application in population ecology (Caswell 1988).…”
Section: Data Assimilation For Models Of Infectious Diseasementioning
confidence: 99%
“…Our estimate of R 0 includes proper estimates of uncertainty, which is rare for estimates in wildlife. We know of only one other instance where this has been done (Miller et al 2006). Credible intervals for R 0 (1.47, 2.32) are not markedly different from the point estimate ;2.5 coarsely derived from assuming that 40% of the adult females are susceptible in a steady-state population (Anderson and May 1991).…”
Section: Understanding Brucellosis In the Yellowstone Bisonmentioning
confidence: 99%
“…CWD can be passed vertically from mother to offspring and horizontally upon direct contact as well as indirectly through contamination of water and feed by saliva and/or feces [5][6][7]. CWD seems more likely to occur where elk or deer are crowded or where they congregate at human-made feed and water stations [8].…”
Section: Isrn Biomathematicsmentioning
confidence: 99%